Central bank reputation, cheap talk and transparency as substitutes for commitment: Experimental evidence - John Michael Duffy; Frank Heinemann (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
We implement a repeated version of the Barro-Gordon monetary policy game in the laboratory and ask whether reputation serves as a substitute for commitment, enabling the central bank to achieve the efficient Ramsey equilibrium and avoid the inefficient, time-inconsistent one-shot Nash equilibrium. We find that reputation is a poor substitute for commitment. We then explore whether central bank cheap talk, policy transparency, both cheap talk and policy transparency or economic transparency yield improvements in the direction of the Ramsey equilibrium under the discretionary policy regime. Our findings suggest that these mechanisms have only small or transitory effects on welfare. Surprisingly, the real effects of supply shocks are better mitigated by a commitment regime than by any discretionary policy. Thus, we find that there is no trade-off between flexibility and credibility.
Keywords: C92; D83; E52; E58; 330; Monetary Policy; Repeated Games; Central Banking; Commitment; Discretion; Cheap Talk; Transparency; Experimental Economics